Civil Society as a Reemerging Instrument of Foreign Policy After Covid-19 - Wara, Yusuf Abubakar; Gül, Serdar Kenan (Eskisehir Osmangazi University Journal of Social Sciences, 2025)
In contemporary times, civil societies, whether focused on charity, humanitarian aid, or development, have been providing more essential services in their countries and the countries they target. Civil societies working in other countries can help home countries advance their foreign policy goals by providing exceptional services, making them an effective soft power tool for enhancing diplomatic relations between nations. This study investigates the strengthening of civil society as a diplomatic strategy in today’s interconnected world, particularly in light of the COVID-19 crisis. The goal is to establish a connection between civil society, soft power, and foreign policy. It also examines the recent effects on foreign policy mechanisms due to the increasing significance of global civil society worldwide.
Keywords: International Institutions; Sivil Toplum; Dış Politika; Araç; İşlevler; İlişkiler; Uluslararası Kuruluşlar; Siyaset Bilimi (Diğer); Civil Society; Foreign Policy; Instrument; Functions; Relations; Political Science (Other)